Molecular pathology : a practical guide for the surgical pathologist and cytopathologist - Bartlett, John M. S.; Shaaban, Abeer; Schmitt, Fernando (Cambridge : Cambridge University Press, 2015)
This practical manual provides a comprehensive yet concise guide to state-of-the-art molecular techniques and their applications. It starts with an overview of the essential principles of molecular techniques, followed by separate chapters detailing the use of these techniques in particular tissues and organs, and describing recommended treatment plans. Each chapter covers the tests available, their advantages, limitations, and use as diagnostic and prognostic tools, with key learning points at the end of each topic. Using both histologic and cytologic samples, it discusses how to interpret test results in a pathologic context and enables trainees and practising pathologists to gain an in-depth understanding of molecular diagnostic techniques and how to incorporate them into routine diagnostic practice. Aiding the daily practice of refining diagnosis, as well as offering a didactic approach, this book is an essential reference for practising pathologists and cytopathologists as well as trainees in pathology.
Machine generated contents note: List of contributors; Preface; 1. An introduction to molecular pathology John M. S. Bartlett; 2. Molecular regulation of cellular function Marsela Braunstein and John M. S. Bartlett; 3. Practical application of molecular techniques in diagnostic histopathology and cytopathology and clinical management Abeer Shaaban and Fernando Schmitt; 4. Fluorescent and non-fluorescent in situ hybridization Jane Bayani and John M. S. Bartlett; 5. Clinical applications of the polymerase chain reaction for molecular pathology Angela B. Y. Hui, Annette D. Wong and Carlo V. Hojilla; 6. Are microarrays ready for prime time? Jane Bayani and John M. S. Bartlett; 7. Tissue microarrays Luigi Tornillo; 8. Sequencing Andrew M. K. Brown, Philipe C. Zuzarte and Paul M. Krzyzanowski; 9. Microsatellite instability in colorectal cancer Maria Sofia Fernandes, Raquel Seruca and Se;rgia Velho; 10. Mutational analysis Aaron R. Hansen, Mahadeo A. Sukhai, Hal K. Berman, Suzanne Kamel-Reid and Philippe L. Bedard; 11. Tumors of the breast Cathy B. Moelans, Petra van der Groep, Robert Kornegoor, Jelle Wesseling and Paul J. van Diest; 12. Tumors of the female genital system Adhemar Longatto Filho, Sigurd F. Lax and Bin Yang; 13. Tumours of the male urogenital system Kirsten D. Mertz and Lukas Bubendorf; 14. Tumors of the gastrointestinal system Manuel Salto-Tellez, Benedict Yan, Roseann I. Wu and Martha Bishop Pitman; 15. Soft tissue, bone and skin tumours Stamatios Theocharis and Jerzy Klijanienko; 16. Cardio-thoracic tumors Umberto Malapelle, Claudio Bellevicine, Elena Vigliar and Giancarlo Troncone; 17. Tumors of the endocrine system Sylvia L. Asa and Ozgur Mete; 18. Haematological malignancies of the lymph nodes Sarah E. Coupland and Pedro Farinha; 19. Pediatric tumors Paul Roberts, Susan Picton and Jens Stahlschmidt; 20. Serous effusions Ben Davidson; 21. Academic applications and future of molecular pathology Manuel Salto-Tellez and Benedict Yan; Index.
Title from publisher's bibliographic system (viewed on 01 Feb 2016).
Keywords: Pathology, Molecular; Molecular diagnosis